Functional characterization of two NAC transcription factors HfNAP1 and HfNAC090 associated with flower programmed cell death in daylily (Hemerocallis fulva) - Wang, Ying (Plant science : an international journal of experimental plant biology, 2023)
Copyright © 2023 Elsevier B.V. All rights reserved.